MITOCHONDRIAL DNA DIVERSITY IN THE GENE POOL OF THE NEOLITHIC AND EARLY BRONZE AGE CISBAIKALIAN HUMAN POPULATION - R. O. Trapezov; A. S. Pilipenko; V. I. Molodin (Вавиловский журнал генетики и селекции)
Molecular analysis of mitochondrial DNA samples (N = 15) of the Neolithic and Early Bronze Age population from the Cis-Baikal region has been performed. East Eurasian haplogroups (D, G2a С, Z, F1b) were identified in the mitochondrial gene pool. The results of phylogeographical analysis suggest that the development of autochthonous East Eurasian genetic components played a major role in the formation of Baikalian populations. Genetic interactions with populations from neighboring regions of Central Asia also contributed to the gene pool structure of the Cisbaikalian population.